Map Projections Cartographic Information Systems - Grafarend, Erik W.; Krumm, Friedrich W. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
In the context of Geographical Information Systems (GIS) the book offers a timely review of map projections (sphere, ellipsoid, rotational surfaces) and geodetic datum transformations. For the needs of photogrammetry, computer vision, and remote sensing space projective mappings are reviewed.